Origami metawall : mechanically controlled absorption and deflection of light - Li, Min (2020)
Metamaterials/metasurfaces, which have subwavelength resonating unit cells (i.e., meta-atoms), can enable unprecedented control over the flow of light. Despite their significant progress, achieving dynamical control of both energy and momentum of light remains a challenge. Here, a mechanically tunable metawall capable of either absorbing light energy or modulating light momentum, by incorporating the magnetic meta-atoms into a 3D printed origami grating, is theoretically designed and experimentally realized. Through mechanical stretching or compressing of the Miura-ori pattern, the function of metawall can transit from an absorber, a mirror, to a negative reflector. Particularly, the continuously geometric deformation of the Miura-ori lattice is a promising approach to compensate the angular dispersion in gradient metasurfaces. Considering the prominent mechanical properties and strong deformation abilities of origami structures, the findings may open an alternative avenue toward lightweight and deployable metadevices with diversified and continuously alterable electromagnetic properties.